Faktor-faktor yang Mempengaruhi Kepuasan Konsumen Terhadap Beras Merah Organik di Kota Denpasar - JESSY VENY OMBUN SIANTURI; I GEDE SETIAWAN ADI PUTRA; WAYAN GINARSA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2013)
ABSTRACT Factors Affecting Consumer Satisfaction Of Organic Red Rice in Denpasar This study aims to find the factors that affect customer satisfaction with organic brown rice in Denpasar and know the level of customer satisfaction with organic brown rice consumed in Denpasar. The research was conducted in Denpasar which took place in two places, gods Tiara Supermarkets and health food stores "Satvika Boga" determined by purposive sampling.The results of this study indicate that the factors that affect customer satisfaction with organic brown rice that is based on the results of a factor analysis of the packaging, taste factors, aroma factors, factors benefits, the availability of, and factors motivating factor perception. The level of customer satisfaction with organic brown rice in the city of Denpasar is, of the 45 respondents, 19 (42.22%) were very satisfied, 15 people (33.33%) were satisfied and 11 (24.45%) were not satisfied . Keywords : satisfaction, consumer, organic